An Industrial-Scale Study of the Hardness and Microstructural Effects of Isothermal Heat Treatment Parameters on EN 100CrMo7 Bearing Steel - Annalisa Fortini; Emanuele Bertarelli; Manuel Cassola; Mattia Merlin (Applied Sciences, 2024)
The 100CrMo7, commonly employed for bearings in rotating machinery, relies on precise heat treatment parameters to ensure an optimal microstructure and, in turn, mechanical properties. Typically, an austenitizing treatment, followed by rapid cooling in a salt bath for martempering or austempering, is crucial in achieving the desired microstructure and hardness. The present industrial-scale study involved a comparative analysis between martempering and austempering routes regarding the hardness and microstructure evolution of EN 100CrMo7 large-size rings. The investigation delves into the effects of austempering temperatures, holding times, and austenitizing temperature. Furthermore, the role of tempering in reducing the amount of retained austenite was also considered. The results indicate that martempering yielded the highest hardness values while austempering exhibited a decrease in hardness at the center of the rings, though a lower amount of retained austenite (in the range of 3.0–4.9 vol.%) was detected in comparison with martempering. In addition, a 850 °C austenitizing temperature reduced the hardness by 16% in the center of the rings and promoted a high content of upper bainite, thus suggesting its inefficacy for the involved large-size rings. In contrast, a 880 °C austenitizing temperature maintained consistently high HRC values across the ring’s height. Lastly, the analysis highlighted that the cooling rate played a more crucial role than the austempering holding time. Such industrial-scale investigations performed on real components improve the knowledge and control of heat treatment parameters in comparison with the nominal guidelines provided by steel suppliers. These outcomes offer insights for optimizing industrial heat treatment parameters, with practical implications for enhancing steel bearings’ microstructural and mechanical performance and lifespan.